(untitled) (Ocean and Coastal Research, 2024)
The Cananéia-Iguape Estuarine-Lagoon Complex (CIELC) is an extremely productive coastal ecosystem. It enclosesthe Valo Grande channel, built 160 years ago, which introduces water from the Ribeira River directly into the estuarinesystem, contributing to important biogeochemical changes in the region. Many nutrients arrive at the estuary throughthis channel, as well as metals and other slightly soluble elements that become part of the sediments. This studyaims to evaluate the processes that govern the distribution of rare earth elements (REE) in the sediments of thecomplex by using fractionation patterns, anomalies, and the geochemical signature of minerals to evaluate sources,natural levels, and the possible anthropogenic forcing to which CIELC is subjected. ∑REE* ranged from 14.2 to 285mg kg-1 and showed a distribution related to depositional/textural characteristics influenced by the regional and locallithological setting and a possible contamination. The REE/Al ratio indicated enrichment in the sea adjacent to theestuary and at stations in the Ribeira River and Valo Grande. While the Hf/Al ratio indicated natural enrichment relatedto the presence of heavy minerals in most of these stations, this ratio fails to justify enrichment at some stations inthe northern part of the estuary and the Ribeira River. Fractionation patterns and anomalies allowed us to identifythe main heavy minerals related to REE enrichment at CIELC. Cerium (Ce) anomalies showed a possible relationwith biologically mediated Ce+3 to Ce+4 oxidation processes in the most productive areas of the estuary. Europium(Eu) anomalies were strongly associated with different mineral assemblies in several CIELC sectors. Abundance,fractionation patterns, and REE anomalies corroborate the categorization of CIELC sediments as part of a pristinesystem in its southern region and as subject to anthropogenic influences in its northern area.